(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: A linguopragmatic analysis of proverbs in English and Uzbek is the study of the linguistic and pragmatic aspects of Proverbs, one of the most ancient and rich forms of folk oral creativity of the two languages. Proverbs are an integral part of language and culture, they reflect not only the lexical and grammatical features of the language, but also its cultural context, social functions. Therefore, the linguistic analysis of Proverbs is considered important in the fields of linguistics and cultural studies.